Fulfilling Education Rights for Girls in Child Marriage to Achieve SDGs Gender Equality - Meliesa Permatahati; Sonny Dewi Judiasih; Nyulistiowati Suryanti (Faculty of Law, University of Mataram, 2023)
The age minimum for marriage in Indonesia is 19 years old for both men and women, but those who are underage can still marry legally by applying for marriage dispensation through a religious court or district court depending on the child’s religion. Child marriage can lead to school dropout since formal school doesn’t accept students who are married so these children will be returned to their parent, most child marriage cases involves girls more than boys which can lead to gender inequality. This research is conducted by a normative juridical method which utilized secondary data resources such as primary, secondary, and tertiary legal materials. Applicable law regarding the right to education for children is studied by referencing marriage law and national educational system law. The method used in this research is descriptive-analytical data including factual behavior in society and verbal respondent’s statement. There are few regulations regarding the right to education for children but in practice, these regulations are difficult to be applied since the school has its authority. In cases like this, there are alternative ways to fulfill the right to education for girls in child marriage as participating in open schools and learning centers held by the community. Gender equality and education are deeply connected and can not be achieved without one another.